Pteridophyte flora of Ayer Hitam Forest Reserve, Selangor, Peninsular Malaysia - Maideen, Haja; Damanhuri, Ahmad; R., Jaman; G., Rusea (Universiti Putra Malaysia Press, 2001)
A total of39 species ojpteridophyte in 22 genera and 15 families has been recorded in Ayer Hitam Forest Reserve, Puchong, Selangor. The list of species prepared was based on collections in study area and previous available data. The diversity of species is low and consistent with the nature of the Forest as a secondary forest.